Factors That Affect Liquidity of Commercial Banks in Kosovo - Morina, Donjeta; Qarri, Albert (European Journal of Sustainable Development, 2021)
A very important factor that affects the growth and survival of commercial banks is also the level of liquidity. Banking industry regulators require banks to possess liquid assets in order to fulfill their obligations to depositors and third parties accurately. Lack of liquidity reduces the ability of banks to meet their obligations and otherwise excess liquidity may be the cause of reduced profits for banks. There are many factors that can affect the position of liquidity in commercial banks and which factors cause unbalanced liquidity and as such also affect their performance. As a result, the study of these factors is of particular importance. The main objective of this study is to analyze the liquidity empathy of the banking sector to several specific banking and macroeconomic factors. To achieve this objective, the study uses regression analysis per a data set that includes a time of 8 years respectively the years 2012 - 2019. To build the necessary econometric model and to achieve the purpose of the study, data are taken from the publications of the Central Bank and the World Bank (GDP data), which data are analyzed for each quarter for the study period. After analyzing the available data, the study concludes that between the main factors that can affect the liquidity position of commercial banks, Non-performing loans, Capital adequacy, and Credit interest rate have the grand and most important impact on the liquidity banking position.